Potential impacts of climate change on precipitation and temperature at Jor Dam Lake - Tayebiyan, Aida; Mohammad, Thamer Ahmad; Ghazali, Abdul Halim; Abdul Malek, Marlinda; Mashohor, Syamsiah (Universiti Putra Malaysia Press, 2016)
Rising global temperatures have threatened the operating conditions of Batang Padang hydropower reservoir system, Malaysia. It is therefore crucial to analyze how such changes in temperature and precipitation will affect water availability in the reservoir in the coming decades. Thus, to predict future climate data, including daily precipitation, and minimum and maximum temperature, a statistical weather generator (LARS-WG) is used as a downscaling model. Observed climate data (1984-2012) were employed to calibrate and validate the model, and to predict future climate data based on SRES A1B, A2, and B1 scenarios simulated by the General Circulation Model's (GCMs) outputs in 50 years. The results show that minimum and maximum temperatures will increase around 0.3-0.7 °C. Moreover, it is expected that precipitation will be lower in most months. These parameters greatly influence water availability and elevation in the reservoir, which are key factors in hydropower generation potential. In the absence of a suitable strategy for the operation of the hydropower reservoir, which does not consider the effects of climate change, this research could help managers to modify their operation strategy and mitigate such effects.